Photosensitizers from Spirulina for Solar Cell - Liqiu Wang; Liang Tian; Xinxin Deng; Mengyi Zhang; Shuping Sun; Wei Zhang; Lin Zhao (Journal of Chemistry)
Spirulina is a kind of blue-green algae with good photosynthetic efficiency and might be used for photovoltaic power generation. So this paper used living spirulina as novel photosensitizer to construct spirulina biosolar cell. The results showed that spirulina had the photoelectric conversion effect, and could let the spirulina biosolar cell have 70 μA photocurrent. Meanwhile, adding glucose sucrose or chitosan in the spirulina anode chamber, they could make the maxima current density of the cell greatly increased by 80 μA, 100 μA, and 84 μA, respectively, and the sucrose could improve the maximum power density of the cell to 63 mW/m−2. Phycobiliprotein played an important role in the photosynthesis of spirulina. So in this paper phycobiliprotein was extracted from spirulina to composite with squaraine dye to sensitize nanocrystalline TiO2 photoanode for building dye sensitized solar cell, and the photoelectric properties of the cell also were investigated.